Ποιότητα Ζωής ενηλίκων ατόμων μετά από νοσηλεία σε Μονάδα Εντατικής Θεραπείας - Γεωργίου, Ανδρέας (Τμήμα Νοσηλευτικής, Σχολή Επιστημών Υγείας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2011)
Background: Patients on long and serious illness, which have borned by the agency, forced to be hospitalized for a long time as in the Intensive Care Unit (ICU). The experience of severe disease and hospitalization in the ICU has long-term effects on the organic and psychological health, both of the patients and his family. Purpose: The purpose of this review is to investigate the Quality of Life (QoL) of adults after hospitalization in the ICU. Specific objectives are, to investigate specific problems in QoL experienced by adults who were hospitalized in ICU for a long time and the factors that contribute to it. Material and Methods: The method used was the search of existing literature databases Pubmed, Cochrane, Cinahl and Internet (Google - Scholar). The keywords used in the search are: intensive care unit, quality of life, and discharge from the ICU. Results: We found 10 quantitative surveys. According to the survey results, the QoL in adults admitted to the ICU is low in the dimensions that constitute it. The most serious problems reported by participants are sleep disturbances, difficulties in concentration and memory of recent events, anxiety / depression, inability to perform usual activities and feeling of discomfort / pain. The factors found to contribute to poor QoL of people admitted to ICU were age, duration of stay in ICU, sex, severity of illness and the lack of social support. Conclusion: More research needs to be done and they must include samples from several countries to assess QoL in adult patients admitted to ICU without interference of other confounding factors such as culture. This will help health professionals to gain a more complete knowledge on this subject, thus helping them in the guidelines which must put in care to deal with the person as a whole.
Keywords: Intensive Care Unit--organization & administration; Quality of life